2016
DOI: 10.1002/lno.10393
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme level N and O isotope effects of assimilatory and dissimilatory nitrate reduction

Abstract: To provide mechanistic constraints to interpret nitrogen (N) and oxygen (O) isotope ratios of nitrate ( NO3−), 15N/14N and 18O/16O, in the environment, we measured the enzymatic NO3− N and O isotope effects (15ε and 18ε) during its reduction by NO3− reductase enzymes, including (1) a prokaryotic respiratory NO3− reductase, Nar, from the heterotrophic denitrifier Paracoccus denitrificans, (2) eukaryotic assimilatory NO3− reductases, eukNR, from Pichia angusta and from Arabidopsis thaliana, and (3) a prokary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 82 publications
(156 reference statements)
5
65
1
Order By: Relevance
“…Similarly, in agreement with Dhondt et al (2003) who measured enrichment factors of ε N = −4.4‰ ± 0.3‰ in hydroponics, plant uptake has been generally associated with minor isotope fractionation compared to denitrification (Denk et al, 2017;Högberg et al, 1999;Lund et al, 1999). In contrast, recent enzymatic assays using eukaryotic NO 3 − assimilatory reductases (Karsh et al, 2012;Treibergs & Granger, 2017) have reported ε N and ε O values as large as ≈30‰. Nonetheless, we are not able to assess either the transferability of such enzyme-level isotope effects to field conditions or the role of the associated eukaryotes for NO 3 − removal at the field site.…”
Section: Uncertainties and Limitationssupporting
confidence: 77%
“…Similarly, in agreement with Dhondt et al (2003) who measured enrichment factors of ε N = −4.4‰ ± 0.3‰ in hydroponics, plant uptake has been generally associated with minor isotope fractionation compared to denitrification (Denk et al, 2017;Högberg et al, 1999;Lund et al, 1999). In contrast, recent enzymatic assays using eukaryotic NO 3 − assimilatory reductases (Karsh et al, 2012;Treibergs & Granger, 2017) have reported ε N and ε O values as large as ≈30‰. Nonetheless, we are not able to assess either the transferability of such enzyme-level isotope effects to field conditions or the role of the associated eukaryotes for NO 3 − removal at the field site.…”
Section: Uncertainties and Limitationssupporting
confidence: 77%
“…However, following the advent of the denitrifier method (18,19), measurements in cultures of both freshwater and marine denitrifying bacteria revealed dual isotope enrichments associated with assimilatory and dissimilatory NO 3 − consumption systematically following linear trajectories of ∼1 (9,10,12,19,20), contrasting with the lower values widely observed in freshwater systems. This invariant coupling of N and O isotopic enrichments has been shown to originate from fractionation during enzymatic bond-breakage (8,21,22), confirmed directly from in vitro enzyme studies of eukaryotic assimilatory and prokaryotic dissimilatory NO 3 − reductases (11,23). Interpretation schemes conventionally ascribed to nitrification are also at odds with isotope systematics uncovered in culture observations.…”
mentioning
confidence: 61%
“…However, the use of 15 N natural abundance to quantify denitrification rates and to constrain N transformation relies heavily on detailed knowledge of the denitrification process and the isotope fractionation involved. The N isotope effect ( 15 ) varies greatly with environmental and experimental conditions and has been reported to range from 5‰ to 40‰ in pure culture studies of heterotrophic denitrifying bacteria (Barford et al, 1999;Dabundo, 2014;Delwiche and Steyn, 1970;Frey et al, 2014;Granger et al, 2008;Hosono et al, 2015;Karsh et al, 2012;Knöeller et al, 2011;Kritee et al, 2012;Treibergs and Granger, 2016;Wunderlich et al, 2012) and in open ocean systems (Brandes et al, 1998;Cline and Kaplan, 1975;Sigman et al, 2005;Sigman et al, 2003;Voss et al, 2001), from 0‰ to 18‰ in continental sediments (Brandes and Devol, 1997;Brandes and Devol, 2002;Dähnke and Thamdrup, 2015;Kessler et al, 2014), from 5‰ to 30‰ in groundwater (Aravena and Robertson, 1998;Böttcher et al, 1990;Fukada et al, 2003;Lehmann et al, 2003;Mariotti et al, 1988;Mengis et al, 1999;Smith et al, 1991;Vogel et al, 1981;Wenk et al, 2014), and from 2‰ to 50‰ in agricultural soils (Blackmer and Bremner, 1977;Chien et al, 1977;Grabb et al, 2017;Lewicka-Szczebak et al, 2014;Lewicka-Szczebak et al, 2015;Mariotti et al, 1981;Mariotti et al, 1982;…”
Section: / 47 1 Introductionmentioning
confidence: 99%
“…Despite numerous studies of the N isotope effect performed using pure cultures of heterotrophic denitrifying bacteria (Granger et al, 2008;Treibergs and Granger, 2016, and references therein), groundwater (Lehmann et al, 2003;Wenk et al, 2014, and references therein), sediments (Dähnke and Thamdrup, 2015;Kessler et al, 2014, and references therein), and agricultural soils (Grabb et al, 2017;Lewicka-Szczebak et al, 2014;Lewicka-Szczebak et al, 2015;Mariotti et al, 1982;Mathieu et al, 2007;Well and Flessa, 2009), only four studies have examined forest soils (Houlton et al, 2006;Menyailo and Hungate, 2006;Perez et al, 2006;Snider et al, 2009).…”
Section: / 47 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation